Incorporación de nuevas herramientas en una aplicación gamificada multiplataforma para la recolección y análisis de datos educativos - Aguilar Ortiz, Keyron Damián (2025)
The project aimed to design, implement, and evaluate functional improvements in the Gamivity platform, focusing on optimizing the gamified learning experience and strengthening teachers’ academic analysis capabilities. The research was conducted with an applied approach, employing the agile Extreme Programming (XP) methodology for software development and the CRISP-DM analytical model for data processing. Quantitative scientific methods and techniques such as brainstorming, collaborative analysis, hierarchical matrix design, structured surveys, and statistical analysis through data pipelines were applied. Technological tools included Laravel, Angular, Flutter, Power BI, and Looker Studio. Among the most relevant results, an optimized authentication system was implemented, a more intuitive mobile interface was developed, and a web-based teacher module with dynamic visualizations integrating key student performance, participation, and progress metrics was added. Academic data analysis enabled the identification of behavioral patterns, areas for improvement, and correlations between performance and participation, supporting evidence-based pedagogical decisions. Technical and usability testing confirmed system stability, scalability, and positive acceptance by end users. In conclusion, the integration of agile methodologies and educational analytics techniques significantly enhanced Gamivity’s functional and pedagogical value, consolidating it as a strategic tool for managing and monitoring learning in gamified virtual environments.